Assessing Problematic Internet Use, Social Media Addiction, Internet Gaming Disorder, and Suicidal Tendencies among Undergraduate Students in a Peripheral Medical College - Khandaker Golam Maruf; Sumitaksha Banerjee; Arunima Chaudhuri (Current Medical Issues)
Background: Problematic Internet use (PIU) and social media addiction (SMA) have emerged as pressing concerns among the youth, with undergraduate medical students being no exception. In addition, Internet gaming addiction is increasingly observed among them. A rise in suicidal tendencies among medical students has also been reported. Objectives: This study aims to explore the correlation between PIU, SMA, Internet gaming disorder (IGD), and suicidal tendencies among undergraduate students of a peripheral medical college. Methodology: A total of 145 students were randomly selected from a batch of 200. Ethical clearance was obtained, and informed consent was secured. Exclusion criteria included refusal to participate, undergoing sleep therapy or medication, and severe illnesses. Data collection was conducted through a Google form, utilizing Young’s Internet Addiction Test (Y-IAT) and the IGD Scale – Short-Form (IGDS9-SF). Results: Mobile phones were the most commonly used device (83.4%). Y-IAT scores indicated that the majority (40.0%) of students exhibited moderate internet addiction, with a mean standard deviation (SD) score of 48.2 ± 18.5. The IGDS9-SF scores suggested that 46.2% of students had minimal gaming addiction. Among participants, 18.6% experienced suicidal thoughts, while 3.4% had attempted suicide, though none was fatal. In addition, 63.4% of students reported seeking mental health support when necessary. Conclusion: A significant proportion of undergraduate medical students engage in PIU and SMA, with some also exhibiting suicidal tendencies.